Intervention research on cultivating psychological resilience in adolescent athletes: an empirical analysis based on mindfulness training - Wang, Shanshan; Liu, Jingwu (Frontiers in Psychology, 2025)
IntroductionPsychological resilience is crucial for adolescent athletes facing competitive pressures, yet effective interventions remain understudied. This study examined the associations between mindfulness training and psychological resilience development in adolescent athletes.MethodsA randomized controlled trial was conducted with 60 adolescent athletes (aged 14-18 years) from a provincial sports school in China. Participants were randomly assigned to an experimental group (n = 30) receiving an 8-week mindfulness training program (90 minutes weekly) or a control group (n = 30) maintaining regular training routines. Psychological resilience was assessed using the Connor-Davidson Resilience Scale at baseline, post-intervention, and 3-month follow-up. Potential moderating effects of gender and training experience were analyzed.ResultsThe experimental group demonstrated significant improvements in total resilience scores from pre-intervention (M = 62.47, SD = 10.21) to post-intervention (M = 75.83, SD = 9.56, p < 0.001, d = 1.35) and follow-up (M = 77.90, SD = 9.14, p < 0.001, d = 1.58), while the control group showed no significant changes. Improvements were observed across all resilience dimensions: personal competence, trust in instincts, positive acceptance of change, and control (all p < 0.001). Neither gender nor training experience significantly moderated intervention effects.DiscussionThese findings provide empirical support for associations between mindfulness training and enhanced psychological resilience in adolescent athletes, with sustained effects at 3-month follow-up. The intervention’s effectiveness across gender and experience levels suggests broad applicability for mental health promotion in youth sports programs. Future research should examine causal mechanisms and long-term sustainability with larger, more diverse samples.